Analisis Perbandingan Pengalaman Pengguna pada Aplikasi Video Conference menggunakan Metode UX Curve (Studi Kasus Zoom dan Meet) - Aisyah Altus Sholikah; Hanifah Muslimah Az-Zahra; Diah Priharsari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Google Meet and Zoom are video conferencing applications that are widely used during the COVID-19 pandemic as an alternative in conducting online activities. Both have differences in features and appearance which certainly make the user experience different. According to this, a study was conducted to compare the long-term user experience on the Google Meet and Zoom applications using the UX Curve method. There are 10 respondents for each application who are active students in the organization. Respondents describe their experiences in a UX curve template with 5 dimensions or points of view: general UX, attractiveness, ease of use, utility, and degree of use. Based on data collection, 50 curves were obtained for each Google Meet and Zoom application. The number of improving curve tendencies generated against Google Meet is more than Zoom, but on the other hand the curve is deteriorating and stable. This shows that Google Meet users are more satisfied with Google Meet, compared to Zoom users towards Zoom itself. This is supported by the percentage of positive reasons obtained for Google Meet, which is 75.2%, while for Zoom it is 73.6%. In addition, the Zoom application is proven to leave more impressions and experiences for users with a greater number of user reasons than Google Meet.